Analytical and numerical investigation of the fluid structure interaction of an elastic beam in a water channel - Fritsche, Manuel; Epple, Philipp; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2020)
The interaction between fluids and solids is becoming increasingly important in the design and analysis of machines, buildings and systems. Due to the fluid-mechanical phenomenon of turbulence and the associated flow and vortex shedding, the fluid structure interaction must be considered, for example, in aircraft wings, civil engineering (e. g. television towers or bridges), the rotor blades of wind turbines or in the field of sensor technology. Due to the increasing computing power, increasingly complex tasks can be calculated with the help of numerical simulations. In this paper, an elastic beam has been defined as test case and has been analyzed in different ways with the methods of the fluid structure interaction (FSI), i.e. with analytical and numerical approaches. For this purpose, the plastic beam has been fixed on one side in a water channel and the flow around it and the beam deflection have been measured. The deformation of the beam due to the flow load around it has been analyzed for varied flow velocities. First, the beam deformation has been estimated based on the analytical equations from structural mechanics and an assumed stagnation pressure on the beam surface. Additionally, the drag coefficient from experimental data of the literature was used to estimate the force on and the bending of the beam. Then two numerical simulations with different FSI coupling methods have been performed with Ansys Workbench 2020 R1. On the one hand, a one-way coupling analysis has been performed in which the pressure field was calculated from the CFD simulation and then transferred to the mechanical analysis. On the other hand, a two-way coupling computation has been performed, which also takes transient effects into account. For this purpose, the flow field and the pressure field have been exchanged iteratively between the fluid and the mechanical solver. This coupling approach is general and corresponds to reality since large deformations and non-linearities are considered. However, this approach always requires a very computation intensive, nonstationary calculation. The results obtained from these parameter studies have then been evaluated and compared in order to determine the accuracy of each analysis methodology. The elaborated results have been discussed and analyzed in detail.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Beam deflection; Fluid-Structure-Interaction; FSI

Development of a Measurement Method for the Classification and Performance Evaluation of Positive Pressure Ventilation (PPV) Fans - Fritsche, Manuel; Epple, Philipp; Delgado, Antonio (Proceedings of the ASME 2018 5th Joint US-European Fluids Engineering Division Summer Meeting. Volume 3: Fluid Machinery; Erosion, Slurry, Sedimentation; Experimental, Multiscale, and Numerical Methods for Multiphase Flows; Gas-Liquid, Gas-Solid, and Liquid-Solid Flows; Performance of Multiphase Flow Systems; Micro/Nano-Fluidics., 2018)
Positive Pressure Ventilation (PPV) fans are used by fire departments. The specified performance data differ depending on the manufacturer, as there is no international and commonly accepted standardized measuring method for evaluating the PPV fan performance. In the present work a new measurement method for the classification and performance evaluation of PPV fans is proposed. These fundamental investigations are based on numerical simulations and experimental test studies. The simulations have been performed with the commercial CFD software ANSYS CFX and the test measurements have been carried out on a newly developed test rig. For the predesign of the measurement method, the flow behavior of a free jet with swirl has been investigated with CFD simulations. A special feature of the PPV fans is that the generated flow rate is not only due to the flow through the rotating impeller, but also a significant flow rate is generated outside the PPV fan due to the viscous shear stresses (principle of a viscous jet pump). For the measurements a new test rig has been designed in order to measure the flow velocity of the PPV fan as it is in real firefighter’s fire combat situations. The new test rig design concept and the numerical and experimental results of these studies are presented in detail in this work.
Keywords: Fans; Performance evaluation; Pressure; Ventilation; Flow (Dynamics); Computational fluid dynamics; Engineering simulation; Impellers; Jet pumps; Shear stress; Warfare

The impact of the gas temperature and of the relative humidity on the performance of fans operating in drying plants - Fritsche, Manuel; Epple, Philipp; Delgado, Antonio (ASME 2018 International Mechanical Engineering Congress and Exposition, IMECE 2018, 2018)